Analysis Of Patients' Decision To Make Return Visits Mitra Sehat KD. Waringin Clinic in 2022 - Afif Wahyudi Hidayat; Lyliana Endang Setianingsih; Emmelia Kristina Hutagaol (Jurnal EduHealth, 2023)
The clinic as one of the health services that plays an important role. Every health institution must be able to prepare the right strategy to attract patient interest, the quality of service is important in influencing patient interest. Based on the quality of health services is strongly influenced by the process of providing health services by health workers. This is because clinical health services have not been able to provide the services that patients really expect. The purpose of this study was to determine the effect of service quality on return visits of outpatients at Mitra Sehat KD. Waringin Clinic 2022. This research is a type of quantitative research with analytic observational design with a cross-sectional design. The sample in this study amounted to 92 people with a purposive sampling technique. The data source in this study is primary data, namely data obtained directly from respondents through research questionnaires. Data were analyzed by chi square test and logistic regression. The results of the research were carried out using the chi-square test and logistic regression with a significance level of p (Sig) <0.05. The results obtained showed that the variable quality of service was related to return visits of outpatients at Mitra Sehat KD. Waringin Clinic. While the results of the logistic regression test showed that the factors of reliability, assurance and responsiveness had an effect on patient visits at Mitra Sehat KD. Waringin Clinic Year 2022. The conclusion from this study is that reliability most influences the return visit of outpatients. The suggestion in this study is to hold a training program in accordance with the needs of health workers to improve the competence and skills of workers so that effective services can be provided and provide opportunities for health workers, especially nurses, to continue their education to a higher level so that they can be more skilled in imparting their knowledge.